The lung in amyloidosis. (6th September 2017) - Milani, Paolo; Basset, Marco; Russo, Francesca; Foli, Andrea; Palladini, Giovanni; Merlini, Giampaolo
Amyloidosis is a disorder caused by misfolding of autologous protein and its extracellular deposition as fibrils, resulting in vital organ dysfunction and eventually death. Pulmonary amyloidosis may be localised or part of systemic amyloidosis. Pulmonary interstitial amyloidosis is symptomatic only if the amyloid deposits severely affect gas exchange alveolar structure, thus resulting in serious respiratory impairment. Localised parenchymal involvement may be present as nodular amyloidosis or as amyloid deposits associated with localised lymphomas. Finally, tracheobronchial amyloidosis, which is usually not associated with evident clonal proliferation, may result in airway stenosis. Because the treatment options for amyloidosis are dependent on the fibril protein type, the workup of all new cases should include accurate determination of the amyloid protein. Most cases are asymptomatic and need only a careful follow-up. Diffuse alveolar-septal amyloidosis is treated according to the underlying systemic amyloidosis. Nodular pulmonary amyloidosis is usually localised, conservative excision is usually curative and the long-term prognosis is excellent. Tracheobronchial amyloidosis is usually treated with bronchoscopic interventions or external beam radiation therapy. Pulmonary amyloidosis is a rare disease that can present as diffuse alveolar-septal, nodular and tracheobronchial http://ow.ly/EKeE30doFxA